Implementation of School and Industry Partnership in Improving Graduates' Competencies: Best Practice at Smk Muhammadiyah 1 Salam Magelang - Hesti Risatina; Bambang Sudarsono; Enung Hasanah (CV. Creative Tugu Pena, 2026)
This study aims to analyze and model best practices for partnerships between schools and the Business and Industry (DUDI) in improving graduate competencies at SMK Muhammadiyah 1 Salam, Magelang. The study used a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results show that the partnership is implemented systematically and integratedly through curriculum synchronization, industry involvement in competency assessment, implementation of industrial work practices (prakerin), on-the-job training (OJT) for teachers, graduate recruitment, and funding and facility support. The findings indicate that the effectiveness of the partnership is not determined by the number of programs, but rather by the level of integration between planning, implementation, evaluation, and graduate transition to the workforce. Curriculum synchronization increases the relevance of learning, while industry involvement in evaluation strengthens the validity of competencies. Experiential learning through prakerin and OJT contributes significantly to strengthening technical skills and work attitudes. This study produces an integrative partnership model that connects the curriculum, industry-based learning, and graduate absorption pathways, so that it can serve as a reference in the development of more relevant and sustainable vocational education.